Analisis Yuridis Kekayaan Intelektual yang Dibebankan Sebagai Jaminan Fidusia Dari Perspektif Ekonomi Kreatif - Febriani, Komang Ari; Sarjana, I Made (Ethics and Law Journal: Business and Notary, 2024)
This writing is intended to analyze and examine the regulation of intellectual property charged as fiduciary collateral in banking credit agreements from the perspective of the creative economy and related to the existence of valuation institutions in assessing the valuation of intellectual property charged as fiduciary collateral in banking credit agreements. This writing applies a normative legal research method based on a statutory approach. The result of the research shows that there is a difference between the Creative Economy Law and the Law on Intellectual Property, causing a blurring of norms. The types of IP that can be used as fiduciary collateral in IP legislation are only copyrights and patents which are regulated in Article 16 paragraph (3) of the Copyright Law and Article 108 paragraph (1) of the Patent Law. However, Article 10 of the Government Regulation of the Creative Economy Law stipulates that IP that can be used as an object of debt collateral is IP that has been recorded or registered in the Ministry of Law and Human Rights and IP that has been managed properly with the explanation that the IP has been commercialized. The obstacle in the execution of IP as fiduciary collateral is related to the existence of valuation institutions that still do not exist and have not been implemented in Indonesia so that banks are still not brave enough to apply IP as fiduciary collateral in credit agreements. Abstrak Penulisan ini ditujukan untuk menganalisis dan mengkaji mengenai pengaturan kekayaan intelektual yang dibebankan sebagai jaminan fidusia dalam perjanjian kredit perbankan dari perspektif ekonomi kreatif dan berkaitan dengan eksistensi dari lembaga valuasi dalam menilai valuasi dari kekayaaan intelektual yang dibebankan sebagai jaminan fidusia dalam perjanjian kredit perbankan. Penelitian ini memakai penulisan dengan metode penelitian hukum normatif berdasarkan pendekatan perundang-undangan. Hasil penelitiannya ialah bahwasanya terdapat perbedaan antara UU Ekonomi Kreatif dengan undang-undang bidang KI sehingga menimbulkan kekaburan norma. Jenis KI yang dapat dijadikan jaminan fidusia dalam perundang-undangan bidang KI hanya hak cipta dan paten yang diatur pada Pasal 16 ayat (3) UUHC dan Pasal 108 ayat (1) UU Paten. Namun dalam Pasal 10 PP Ekraf mengatur bahwa KI yang dapat dijadikan objek jaminan utang yaitu KI yang sebelumnya dicatatkan atau didaftarkan pada Kemenkumham dan KI yang sudah dikelola dengan baik dengan penjelasan bahwa KI tersebut sudah dikomersialisasikan. Adapun kendala dalam eksekusi KI sebagai jaminan fidusia yaitu berkaitan dengan keberadaan lembaga valuasi yang masih belum ada dan belum diterapkan di Indonesia sehingga bank masih belum berani menerapkan KI sebagai jaminan fidusia dalam perjanjian kredit. Kata Kunci: Kekayaan Intelektual, Jaminan Fidusia, Ekonomi Kreatif.